Analysis of the Influence of Service Quality, Price, and Facilities on Customer Satisfaction: A Case Study at PT. J&T Express - Alirejo, Mohamad Subroto (CV. HEI PUBLISHING INDONESIA, 2025)
Customer satisfaction is a key indicator of long-term success in the logistics industry. This study aims to empirically examine the simultaneous influence of service quality, price, and facilities on customer satisfaction among PT's customers. J&T Express, a major courier company operating amid Indonesia’s rapid e-commerce expansion. Data were collected from 200 active customers via a quantitative, cross-sectional survey. Service quality was measured using an adaptation of the five SERVQUAL dimensions. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4.0. Results indicate service quality is the strongest predictor of customer satisfaction (β = 0.46, p < 0.001), followed by price (β = 0.32, p = 0.004) and facilities (β = 0.21, p = 0.012). The structural model explains 62% of the variance in customer satisfaction (R² = 0.62). Further analysis revealed that responsiveness and tangibles were the most influential subdimensions of service quality. These findings suggest that PT. J&T Express should prioritize improving service responsiveness and physical service evidence while maintaining competitive pricing. This study provides empirical evidence on the relative importance of satisfaction determinants in the courier service industry and offers practical guidance for enhancing services.